Sea gardens of the aegean - Eleftheriou, Tassos; Kallergis, Manolis (Institute of Marine Biology of Crete, 2002)
A truly international achievement: The scientists of Marine Biology of Crete, while monitoring and analysing underwater events during the course of their scientific work in the waters of Aegean, brought back unique footage recording a beautiful and fragile environment in the thoes of rapid ecosystem changes. "Sea gardens of the Aegean", reveals the beauties of the marine world of thw Aegean, where only a few metres below the surface sea plants grow in profusion, luxuriant meadows of the sea grass darting fish and strange sea animals frolic on the sands or lurk in hidden depths.